Students’ Perception on Incorporating Local Wisdom into Creative Writing Class: Impressions and Facts - Lekawael, Rosina; Que, Stella Rose; Aritonang, Parjolo; Ngadjen, Syahdania Aini (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2025)
This study investigates students' perceptions of integrating local wisdom into creative writing, focusing on poetry in the Indonesian educational context. The research employs a mixed-method approach, combining quantitative data from surveys and qualitative insights from interviews, to explore students’ experiences, engagement, and challenges in writing poetry that reflects their cultural heritage. Findings reveal that while students generally perceive local wisdom integration positively, enhancing both cultural connection and creative expression, they also face notable challenges, particularly related to language translation and personal relevance. The study underscores the need for culturally responsive pedagogy that balances local content with creative freedom, fostering deeper engagement in creative writing education.